Lembaga Zakat, Infaq, Sedekah dan Waqaf (ZISWAF) Pengertian dan Fokus - Siti Nur Rohmah; Wanda Maulidah Awali; M. Luthfi Muwaffiq; Shofia Husna (Pusat Riset dan Inovasi Nasional, 2025)
The Islamic economic system emphasizes the principle of wealth distribution that is fair and equitable through the institutions of Zakat, Infaq, Sedekah, and Wakaf (ZISWAF). ZISWAF plays a role as a social instrument to improve community welfare and reduce economic disparities. Zakat is an obligation for Muslims who are capable, while infaq and sedekah are voluntary forms of social concern that can be performed at any time. Wakaf, with its focus on sustainability, has significant potential to support long-term development through the management of assets for public benefit, such as in education and healthcare. Through professional, transparent, and accountable management, ZISWAF can have a significant impact on poverty alleviation, reduce social inequality, and strengthen an economy based on Islamic values. ZISWAF management institutions such as BAZNAS and Dompet Dhuafa play an important role in economic empowerment programs, social assistance distribution, and the management of productive waqf. This article aims to provide a comprehensive understanding of the ZISWAF concept and explain the role of each component in the Islamic social finance system, as well as highlight the potential of ZISWAF in creating a just, independent, and sustainable economy in Indonesia.